Adherence to treatment with imatinib in chronic myeloid leukemia: a study of the first decade of responses obtained at a Brazilian hospital - Reis,Samuel Roosevelt Campos dos (2013)
Objetive: The aim of this study was to identify the reasons for failure in adherence to imatinib mesylate treatment in chronic myeloid leukemia. Methods: A retrospective review was performed of 100 non-electronic records of patients with Ph+ chronic myeloid leukemia treated with imatinib mesylate. The study period was from January 2001 to January2011. Data were analyzed by Chi-Square and Correspondence analysis using the Statistical Analysis System software package. Results: At the beginning of treatment 41% of patients were in advanced stages of the disease. The unavailability of the drug (44.8%) and myelotoxicity (25.7%) were the most frequent reasons for interruption. The adherence rate was < 90% in 47% of the cases. The low adherence influenced the cytogenetic response (p-value = 0.020) and molecular response (p-value = 0.001). Very high adherence (> 95%) induced complete cytogenetic response, major cytogenetic response and major molecular response. Conclusion: The population of this study obtained lower-than-expected therapeutic responses compared to other studies.